Upaya Meningkatkan High Order Thingking Skill (HOTS) Siswa dalam Pembelajaran Sosiologi Melalui Penerapan Strategi PBL Kelas XI IPS SMAN 1 Ulakan Tapakis, Padang Pariaman - Zulvia, Reka; Junaidi, Junaidi (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This research is motivated by the low learning outcomes of students' HOTS in learning sociology class XI IPS SMAN 1 Ulakan Tapakis. One of the reasons for the low HOTS results is the selection of an inappropriate strategy chosen by the teacher in training students' HOTS. For the solution that is given in increasing students' HOTS, namely by applying problem based learning strategies in sociology lessons. This study aims to improve students' HOTS through problem based learning or PBL strategies in sociology learning. This research is a classroom action research (CAR) conducted in 2 cycles consisting of 4 stages of research, namely planning, implementation, observation and reflective. This research was conducted in class XI IPS 1 SMAN 1 Ulakan Tapakis, Padang Pariaman which was carried out directly in class. This study uses research instruments using observation sheets, field notes and student response questionnaires. In seeing the increase in student learning outcomes, they use questions that are done at the end of the cycle. In seeing the progress of students' HOTS results by using the formula P=F/NX100. The target of this research is to reach the good category, which is at 61% -80%. The results showed that there was an increase in learning outcomes using the PBL strategy with the results of an increase in the results of the pre-action test and cycle 1, which increased from 3.22% to 41.93% with an increase of 38.71% while the results of the second cycle were 77.45% with an increase of 36.42%. So that the results of the research in the second cycle have reached the target, which is in the good category of 61% -80%. The results shiwed that there was an increase in learning outcomes using the PBL startegywith the results ofan increase in the per-action tes and cycle I, which increased from 3,22% to 41,93% with an increase of 38,71%, while the results of cycle II has reached thetarget, which is in the good category 61%-80%.